Emotional Factors, Product Quality and Service Quality on Customer Satisfaction Of Kedai Pagii Sore in Nganjuk - Tribuanawati, Octarina; Dian Kusumaningtyas (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to determine whether there is an influence between emotional factors, product quality and service quality on customer satisfaction at Kedai Pagii Sore in Nganjuk. Design/Methode/Approach This study uses a quantitative approach with a total sample of 100 respondents with sampling techniques using purposive sampling. While the data analysis techniques used in this study are t test, F test, classical assumption test, descriptive analysis test, and crosstabulation test. Research Finding : This study shows that emotional factors, product quality and service quality have a significant effect on customer satisfaction at Kedai Pagi Sore in Nganjuk, with product quality having the most dominant effect. At the same time, the three factors explain 35.8% of the variability in customer satisfaction.This study also provides theoretical contributions by including the role of emotional factors and practical recommendations to improve product quality, service and emotional experience to maximise customer satisfaction.